Math Problems

MathematicsPrecalculusLinear Equations → Linear Equation

Solve for the variable in the linear equation

## Questions

 $$- 3 b - 4 = - 4 b - 6$$ $$9 - 3 y = 4 - 2 y$$ $$4 - y = 1 - 5 y$$ $$- 3 c - 3 = - 6 c - 6$$ $$6 - 2 b = 5 - 5 b$$ $$4 b - 1 = 3 - b$$ $$7 - 3 x = 2 - 5 x$$ $$- 3 x - 6 = 2 x - 3$$ $$- 5 b - 1 = - 4 b - 6$$ $$2 c + 3 = 6 c - 3$$ $$2 - 3 y = 1 - 7 y$$ $$c - 7 = 3 c - 4$$ $$5 b - 8 = 4 b - 5$$ $$1 - 5 x = - 6 x - 2$$ $$- 2 b - 1 = - 4 b - 4$$ $$- 5 y - 6 = -1$$ $$9 - b = 4 - 4 b$$ $$6 - x = 4 - 6 x$$ $$- 6 x - 4 = - 11 x - 2$$ $$- 5 y - 8 = - 6 y - 5$$ $$2 c + 5 = 7 c + 1$$ $$4 x + 7 = 9 x + 3$$ $$4 c - 2 = 8 c + 3$$ $$-3 = 5 a - 6$$ $$- y - 7 = y - 6$$ $$5 - 6 b = - 11 b$$ $$8 - 6 x = 5 - 4 x$$ $$10 - x = 5 - 6 x$$

 $$- 3 b - 4 = - 4 b - 6$$ ⇒ $$b = -2$$ $$9 - 3 y = 4 - 2 y$$ ⇒ $$y = 5$$ $$4 - y = 1 - 5 y$$ ⇒ $$y = - \frac{3}{4}$$ $$- 3 c - 3 = - 6 c - 6$$ ⇒ $$c = -1$$ $$6 - 2 b = 5 - 5 b$$ ⇒ $$b = - \frac{1}{3}$$ $$4 b - 1 = 3 - b$$ ⇒ $$b = \frac{4}{5}$$ $$7 - 3 x = 2 - 5 x$$ ⇒ $$x = - \frac{5}{2}$$ $$- 3 x - 6 = 2 x - 3$$ ⇒ $$x = - \frac{3}{5}$$ $$- 5 b - 1 = - 4 b - 6$$ ⇒ $$b = 5$$ $$2 c + 3 = 6 c - 3$$ ⇒ $$c = \frac{3}{2}$$ $$2 - 3 y = 1 - 7 y$$ ⇒ $$y = - \frac{1}{4}$$ $$c - 7 = 3 c - 4$$ ⇒ $$c = - \frac{3}{2}$$ $$5 b - 8 = 4 b - 5$$ ⇒ $$b = 3$$ $$1 - 5 x = - 6 x - 2$$ ⇒ $$x = -3$$ $$- 2 b - 1 = - 4 b - 4$$ ⇒ $$b = - \frac{3}{2}$$ $$- 5 y - 6 = -1$$ ⇒ $$y = -1$$ $$9 - b = 4 - 4 b$$ ⇒ $$b = - \frac{5}{3}$$ $$6 - x = 4 - 6 x$$ ⇒ $$x = - \frac{2}{5}$$ $$- 6 x - 4 = - 11 x - 2$$ ⇒ $$x = \frac{2}{5}$$ $$- 5 y - 8 = - 6 y - 5$$ ⇒ $$y = 3$$ $$2 c + 5 = 7 c + 1$$ ⇒ $$c = \frac{4}{5}$$ $$4 x + 7 = 9 x + 3$$ ⇒ $$x = \frac{4}{5}$$ $$4 c - 2 = 8 c + 3$$ ⇒ $$c = - \frac{5}{4}$$ $$-3 = 5 a - 6$$ ⇒ $$a = \frac{3}{5}$$ $$- y - 7 = y - 6$$ ⇒ $$y = - \frac{1}{2}$$ $$5 - 6 b = - 11 b$$ ⇒ $$b = -1$$ $$8 - 6 x = 5 - 4 x$$ ⇒ $$x = \frac{3}{2}$$ $$10 - x = 5 - 6 x$$ ⇒ $$x = -1$$